Some notes on matrix transforms of summability domains of Cesàro matrices - Aasma, Ants (Mathematical Modelling and Analysis, 2010)
In this paper sufficient conditions for a matrix M = (mnk ) (mnk are Cesàro numbers As n‐k, s ∈ C if k ≤ n and mnk= 0 if k > n) to be a transform from the summability domain of the Cesàro method Cα into the summability domain of another Cesàro method Cβ , where α, β ∈ C{-1, -2,…, are found. First published online: 09 Jun 2011